(3GdCTHGg hGdfXGFQ GdfMhjIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3SHMGf Gddg GdefRg Yf GdCTHGg hGdfXGFQ hGdMeO ddg CeG HYO aEf afhf GdYQHjI Ydi GNJdGa CfhGYgG gi Chd afhfi s
(3BNQgG (B:s
(3Ch ehUhdI Ch RGFOI agi WGQFI Ydjg bWYkG hjhLH UHQ ZjQ GdefUQa LRekG cedJ GdCTHGg hGdfXGFQ GdfMhjI s
(3HgG fXGe GdJYbjHIs
(3UaMI GdYfhGf eMdGg HGdPgH hYdjgG ELGRI HGdcJGH ef GdTjN MSf eMeO GdYWGQ djTjN GdESdGe CMeO YGQa MceJ RGOgs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI(B((3fMh (B1) s
Keywords: (3GdfMhs